Gallbladder cancer during pregnancy treated with surgery and adjuvant gemcitabine: A case report and review of the literature - Diciolla, A.; Gianoni, M.; Fleury, M.; Szturz, P.; Demartines, N.; Peters, S.; Duran, R.; Desseauve, D.; Panchaud, Monnat A.; Fasquelle, F.; Digklia, A. (Frontiers in Oncology, 2022)
Background Gallbladder cancer (GBC) represents the most common biliary tract cancer. Prognosis remains poor with 5-year overall survival rates less than 5% in advanced stages. GBCs are diagnosed more frequently in women, supposedly due to endocrine factors. Case A 35-year-old woman, diagnosed with a non-metastatic GBC in the 22nd week of gestation, underwent a complete surgical resection 5 weeks later. Adjuvant gemcitabine was administered without complications, temporarily discontinued in the 32nd week to allow childbirth. The patient was disease-free for more than 3 years with ongoing remission at the last visit in July 2022. During the follow-up period, the child had no developmental, cognitive, or other health issues. Conclusion Malignant tumors occur in about 0.1% of pregnant women, many are treated with chemotherapy. In oncology, the need to deliver optimal treatment in these patients represents a major concern. Both surgery and adjuvant chemotherapy of locally advanced GBC can be performed safely, with certain considerations, in the second trimester of pregnancy.